PENGARUH PERMAINAN TRADISIONAL LOMPAT KARET (YEYE) TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK BAITUL MAKMUR DESA TEBING-TINGGI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Oktalia, Berti; Indarto, Wusono; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations of the gross motor development of children is still before the treatment is given in the form of traditional games jump rubber activity (yeye) is low and teachers are still using methods that dominate and not varied. This means that the need for stimulus is given to children to improve gross motor development activities in the form of a rubber jump (yeye). This study aims to determine the gross motor skills of children aged 5-6 years in kindergarten Baitul Makmur village-Tebing subdistrict Benai Regency Kuantan High Singingi before being given a traditional game of jumping rubber (yeye). The sample in this study amounted to 20 children comprising eight boys and 12 girls aged 5-6 years. In this study, researchers gathered data from the measuring instrument research, observation and documentation. Statistical test with t-test = -24.903 and p = 0.000. Because p <0.05 then can researchers conclude that there is a difference in gross motor development of children is very significant between before and after the application of rubber jumping activities (yeye). So it means Ho rejected and Ha accepted which means no difference before and after treatment. According to the table in the value of the t distribution, when df 19, to test the p ihak with a standard error of 5%, then the price of the t-table = 1.740. If the t-count fell to the reception area Ha, Ha stating the gross motor development of children after treatment is higher than before the treatment received. Based on the calculations, it turns out the price of -24.903 t fall on acceptance or rejection Ha Ho. Thus it can be concluded that there are significant differences in gross motor development of children before and after treatment, in which the gross motor development of children is higher after treatment than before treatment